2020
DOI: 10.1016/s1470-2045(19)30817-4
|View full text |Cite
|
Sign up to set email alerts
|

Fulvestrant plus capivasertib versus placebo after relapse or progression on an aromatase inhibitor in metastatic, oestrogen receptor-positive breast cancer (FAKTION): a multicentre, randomised, controlled, phase 2 trial

Abstract: Background Capivasertib (AZD5363) is a potent selective oral inhibitor of all three isoforms of the serine/threonine kinase AKT. The FAKTION trial investigated whether the addition of capivasertib to fulvestrant improved progressionfree survival in patients with aromatase inhibitor-resistant advanced breast cancer.Methods In this randomised, double-blind, placebo-controlled, phase 2 trial, postmenopausal women aged at least 18 years with an Eastern Cooperative Oncology Group performance status of 0-2 and oestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
141
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(154 citation statements)
references
References 33 publications
(42 reference statements)
0
141
0
5
Order By: Relevance
“… 22 , 23 Capivasertib plus fulvestrant might be efficacious in endocrine-resistant oestrogen receptor-positive breast cancer without mutation selection, as shown in the FAKTION trial. 24 It is not possible to robustly compare plasmaMATCH with FAKTION, as patients enrolled in plasmaMATCH had more previous lines of treatment, and AKT1 mutations were not assessed and would be few in number in FAKTION. 24 …”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 Capivasertib plus fulvestrant might be efficacious in endocrine-resistant oestrogen receptor-positive breast cancer without mutation selection, as shown in the FAKTION trial. 24 It is not possible to robustly compare plasmaMATCH with FAKTION, as patients enrolled in plasmaMATCH had more previous lines of treatment, and AKT1 mutations were not assessed and would be few in number in FAKTION. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Loss or inactivation mutation of PTEN (ESCAT Tier IIA) is a crucial step during breast carcinogenesis as PTEN is a negative regulator of PI3K pathway; PTEN acts as a direct antagonist of PI3K through dephosphorylation of PIP3. PTEN loss results in AKT-mTOR signaling activation, and capivasertib (AZD5363), an AKT inhibitor, can suppress the aberrant pathway [30]. In current study, 23 breast cancers harbored PTEN mutations, and capivasertib combined with fulvestrant or chemotherapy might be a choice of refractory diseases depending on hormone receptor status.…”
Section: Discussionmentioning
confidence: 85%
“…After screening the titles and abstracts, 124 remaining records were considered to be eligible for a full text review. Ultimately, 35 articles were selected which met all the inclusion criteria, giving a total of 12,285 patients involved in this network meta-analysis, as shown in [ 7 8 12 13 14 15 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 ]. The search process based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) technique is shown in in Figure 1 [ 48 ].…”
Section: Resultsmentioning
confidence: 99%